Comparison of placement characteristics using two intraosseous devices in canine and feline cadavers by novice users - Uzan, Olivia C.; Guieu, Liz S.; Hall, Kelly E.; Tucker, Claire D.; Webb, Tracy L.; Dunn, Julie; Guillaumin, Julien (Frontiers in Veterinary Science, 2023)
A battery-powered IO device (BPIO) utilized in veterinary practice is reliable in facilitating IO catheter placement. A new spring-powered IO device (SPIO) has been developed for people but has not been tested in veterinary patients. The goal of our study was to compare placement characteristics and flow rates achieved with the BPIO compared to the SPIO in animals when operated by novice users. Six veterinary students performed 72 catheterizations in the humeri and tibias of 12 dog and 6 cat cadavers. The user, cadaver, device, and site of placement were randomized. Flow rates were determined by three-minute infusions. In dogs, overall success rates (50% BPIO, 46% SPIO; p=0.775) and flow rates based on location were similar between devices.Successful placement was faster on average with the BPIO (34.4 seconds for BPIO and 55.0 seconds for SPIO, p=0.0392). However, time to successful placement between devices was not statistically significant based on location (humerus: 34.7 seconds for BPIO and 43.1 seconds for SPIO, p=0.3329; tibia: 33.3 seconds for BPIO and 132.6 seconds for SPIO, p=0.1153). In cats, success rates were similar between devices (16.7% for BPIO and 16.7% for SPIO, p=1.000), but limited successful placements prevented further analysis. This is the first study to examine the use of the SPIO in animals, providing preliminary data for future IO studies and potential applications for training in the clinical setting.